Ressonâncias órficas em Os quatro cantos do tempo de David Mourão-Ferreira - Costa, Gustavo Machado (2008)
This work aims to analyze Orpheu myth s ressonances in Os quatro cantos do tempo, by portuguese writer David Mourão-Ferreira. The study is divided into three chapters. Chapter one intends to discuss the place of David Mourão-Ferreira in the portuguese contemporary poetry tendency s. Next, this chapter observe critics consideration s about elements of classical tradition in David Mourão-Ferreira poetry s. Chapter two describes the principal components of Os quatro cantos do tempo in order to identify wich relate to Orpheu myth s. The third chapter discuss the orphic ressonances in the book. This chapter investigate the assimilation of magic verb in modern poetry and in Mourão-Ferreira poetry s. Besides, It searches how Orpheu and Eurydice adventure s is figurated in the book.